REALIZING A SINGLE-STAGE HYBRID PV SYSTEM USING BATTERY CURRENTSHARING POWER DECOUPLING METHOD - Kumar, Pujari Harish; Kumar, Marathi Rakesh; Sreedhar, Dr. Manda; Naidu, Lingutla Ramesh (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2018)
Conventionally, the single-stage grid-connected PV inverter needs a large PV-side electrolytic capacitor to suppress the doubleline frequency current ripple to keep the PV operating at maximum power point (MPP). However, the short lifetime electrolytic capacitor will reduce the PV inverter’s reliability dramatically. In order to overcome the above problem, a novel battery currentsharing power decoupling (BCSPD) method for hybrid photovoltaic (PV) power systems is proposed in this paper. The proposed BCSPD circuit is parallel-connected with the string PV module to achieve as a single-stage topology. Thus, a high power conversation efficiency can be obtained. The current-injection method is adapted to solve the current ripple problem. Therefore, the required capacitance in PV side can be greatly reduced, so long-life film capacitors can be used instead of electrolytic capacitors. In addition, the battery storage system with the droop control is also used to realize the power regulation function to meet the requirements of actual applications. A 1200 W prototype was designed and implemented to assess the system performance. Experimental results show that the proposed system can track MPP, regulate the load power condition, and reduce current ripple.